The Relationship between Financial Risks and Commercial Banks' Performance in Malaysia - Mohamad Razim Ikmal, Idris; Norlina, Kadri; Mohd Waliuddin, Mohd Razali (UNIMAS Publisher, 2024)
This research examines the relationship between financial risks and the performance of commercial banks in Malaysia from 2018 to 2022. Financial risks considered include operational risk, credit risk, and liquidity risk. The study aims to identify how these risks impact the efficiency and stability of commercial banks, and how such risks influence investor confidence and capital inflows. Using data from various Malaysian commercial banks, this study employs regression analysis to assess the significance and strength of the relationships between different types of financial risks and bank performance. The findings contribute to a better understanding of the financial dynamics within the Malaysian banking sector, providing valuable insights for investors and financial analysts to make informed decisions. This research is crucial given the increased financial uncertainties and economic challenges in the post- COVID-19 era.